RAD6B Plays a Critical Role in Neuronal DNA Damage Response to Resist Neurodegeneration - Guo, Zhao; Tian, Yingxia; Guo, Yingli; Li, Boya; Liu, Xiangwen; Xie, Kun; Song, Yanfeng; Wang, Degui (Frontiers in Cellular Neuroscience, 2019)
RAD6 participates in DNA double-strand breaks (DSBs) repair by ubiquitinating histone H2B in mitotic cells. In terminally differentiated cells, however, the mechanisms of DNA damage repair are less well known. In this study, we investigate whether RAD6B is involved in DSBs repair in neurons and effects of RAD6B deficiency on neuronal survival. We compared neurons of RAD6B-deficient mice with those of littermate wild type (WT) mice and induced DNA damage by X-ray irradiation. We provide evidence that RAD6B is essential for neural DDR and RAD6B deficiency results in increased genomic instability and neurodegeneration. Moreover, higher levels of p53 and p21 are present in the brains of RAD6B-deficient mice, which may be responsible for neuronal senescence and degeneration. In addition, behavioral experiments show that RAD6B-deficient mice exhibit marked learning and memory deficits. In conclusion, these findings suggest that RAD6B is critical for neural integrity and that the absence of RAD6B accelerates neurodegeneration in mice.